2011
DOI: 10.1063/1.3646510
|View full text |Cite
|
Sign up to set email alerts
|

Robust conductance of dumbbell molecular junctions with fullerene anchoring groups

Abstract: The conductance of a molecular wire connected to metallic electrodes is known to be sensitive to the atomic structure of the molecule-metal contact. This contact is to a large extent determined by the anchoring group linking the molecular wire to the metal. It has been found experimentally that a dumbbell construction with C60 molecules acting as anchors yields more well-defined conductances as compared to the widely used thiol anchoring groups. Here, we use density functional theory to investigate the electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 36 publications
(38 reference statements)
8
25
0
Order By: Relevance
“…First, we find that the current is mainly carried by the HOMO of the BDC60, while in Ref. 54 it was found that the transport is dominated by the LUMO. Let us stress that we have confirmed the level alignment described above by test calculations with even larger gold clusters (116 atoms).…”
Section: C 60 As An Anchoring Groupmentioning
confidence: 94%
See 1 more Smart Citation
“…First, we find that the current is mainly carried by the HOMO of the BDC60, while in Ref. 54 it was found that the transport is dominated by the LUMO. Let us stress that we have confirmed the level alignment described above by test calculations with even larger gold clusters (116 atoms).…”
Section: C 60 As An Anchoring Groupmentioning
confidence: 94%
“…We have chosen this molecule for several reasons. First, it has been investigated both experimentally 7 and theoretically, 53,54 which allows us to establish a comparison with our results. Second, the transport through the central moiety (a phenyl ring) can be analyzed with other anchoring groups, which is necessary to determine the quality of C 60 as a terminal group.…”
Section: C 60 As An Anchoring Groupmentioning
confidence: 99%
“…In accordance with the structure of the SAM, we use a model for the spectral density, where the matrix elements of α , represented in a local basis of atomic orbitals, are given by ( α ) nn = 1 eV for orbitals n corresponding to the outermost hexagon of carbon atoms of the C 60 head groups at the left and right boundary of the SAM and ( α ) nn = 0 otherwise. This value is a reasonable choice for molecule-gold contacts [24,25]. The conformational sampling of the SAM is based on classical atomistic MD simulations described in detail previously [15,23].…”
Section: Resultsmentioning
confidence: 99%
“…32,33,37 Theoretical calculations have demonstrated that the conductance of these molecules is dominated by the alignment of LUMO orbitals with the electrode Fermi levels. 38 Using a scanning tunneling microscopy (STM) setup, Leary et al 33 and Gillemot et al 37 were able to image individual dumbbell molecules attached to gold substrates, and recorded subsequently the current through isolated, single molecular nanojunctions by gently touching one of the bulky C 60 anchoring groups with the STM tip. More than one conductance state was found in these investigations.…”
Section: Introductionmentioning
confidence: 99%